The Ongoing Quest for Culturally-Responsive Assessment for Indigenous Students in the U.S. - Trumbull, Elise; Nelson-Barber, Sharon (Frontiers in Education, 2019)
ABSTRACT The Ongoing Quest for Culturally-Responsive Assessment for Indigenous Students in the U.S. Elise Trumbull and Sharon Nelson-Barber Efforts in the U.S. to design curriculum, instruction, and assessment based on Indigenous systems of knowledge and ways of teaching and assessing learning have been mounted wherever Indigenous peoples live. This article discusses ongoing issues in the assessment of Indigenous students in the U.S. and elsewhere, offers examples of promising efforts along with steps toward better policies and practices, explores the concept of “culturally-valid assessment,” and interleaves recommendations for going forward constructively. We provide examples from our own research and other professional experiences of the past two plus decades—primarily in the U.S. (including Alaska and Hawaiʻi), and also in the US-affiliated entities in Micronesia. We address culturally-responsive instruction and argue that assessment should be connected to what and how students have learned in the classroom.